Factors determining acquisitions of companies in Slovenia - Matej Lahovnik (Journal for East European Management Studies, 2000)
This paper deals with some specific characteristics of the acquisition strategy in the Slovenian economy. Some characteristics cannot be compared with Western European developed economies; such characteristics include the incomplete privatisation process, the underdeveloped financial and labour markets and certain structural changes. The purpose of this paper is to highlight these characteristics and to reveal some main factors that motivate the companies to develop the strategy of acquisition in the Slovenian economy in its transition period. In this paper the results of the empirical research into factors determining the acquisitions in Slovenia are to be presented. The respondents were managing directors of 62 large Slovenian enterprises. The basic statistical measure is weighted average. The dispersion of the assessment is described by calculating standard deviation. – – Dieser Artikel setzt sich mit einigen spezifischen Merkmalen der Übernahmestrategien in Slowenien auseinander. Einige dieser Merkmale koennen jedoch nicht mit dem westeuropaeischen Wirtschaftsraumverglichen werden: z.B. dem Privatizationsprozess und den bestimmten strukturellen Änderungen. Dem Artikel liegt die Absicht zugrunde, spezifische Merkmale der Übernahmestrategien in Slowenien zu definieren und Motive fuer die Firmenübernahme im slowenischen Wirtschaftsraum festzulegen, und zwar in der Zeitspanne des Transitionsprozesses. Die Ergebnisse basieren auf der Befragung von Geschäftsführern von 62 Großfirmen. Als statistisches Maß gilt der gewichtete Durchschnitt. Die Dispersion der Bewertung ist durch die Standarddeviation ausgemessen.
Keywords: 650